Invited Commentary: Sibling-Comparison Designs, Are They Worth the Effort? - Frisell, Thomas (Am J Epidemiol, 2020)
In this issue of the Journal, von Ehrenstein et al. (Am J Epidemiol. 2021;190(5):728–737) add to the large and growing literature on the potentially causal association between prenatal exposure to maternal smoking and neuropsychiatric health. In addition to statewide, prospectively collected data, a particular strength was their ability to perform a sibling-comparison design, contrasting the rate of autism spectrum disorder in siblings discordantly exposed to maternal smoking. Unfortunately, the estimate from the sibling pairs could neither confirm nor refute the conclusions based on the full cohort. Interpretation was hampered by broad confidence limits, and even had power been higher, the authors acknowledge a range of potential biases that would have made it difficult to draw any firm conclusions from a similarity or difference in the sibling-pair estimate and estimate from the full cohort. Was the addition of the sibling comparison actually worth the effort? In this commentary, I will briefly summarize the benefits and limitations of this design, and, with some caveats, argue that its inclusion in the study by von Ehrenstein et al. was indeed a strength and not just an ornamentation.